STILISTIKA NOVEL PARA PRIYAYI KARYA UMAR KAYAM - Mukminin Mukminin (EDU-KATA, 2014)
The purpose of this study are (1) to describe the diction in The Priyayi novel by Umar Kayam, (2) To describe the style of the sentence in The Priyayi novel by Umar Kayam, (3) To this style of figurative language in The Priyayi novel by Umar Kayam, (a) Describe the personification style, (b) describe the style Simile, (c) Describe the metaphor, (4) To describe aspects of the imagery in the novel The Priyayi by Umar Kayam, (5) To describe the rhetorical devices in novel The Priyayi by Umar Kayam. The research uses descriptive qualitative method-semoitik structuralism and hermeneutic techniques. This is done because analyzing a novel is hard to avoid the use of integrated methods so that it is impossible to use.The results First assessment functions at the levelof stylistic choice of words (diction elements) have a relationship with the characters and background. As the principle of structuralism, that there is relation between the elements, style (in this case the diction), characters, and relation between ground. Second, study the style of sentences back long sentences authors used primarily to describe the atmosphere. describes a state that is of nature, or describe characters. And the choice of using short sentences have the effect of simplicity. Third, study the style of figurative language (figurative) are purposely created to obtain the aesthetic effect to describe the background of the story. Fourth, the study of images in the novel The images contained Priyayi novel contains vision and color images of (local color) is usedto emphasize the background of story and aesthetically asspect so the reader as if saw for theirself. Fifth, in The Priyayinovel rhetorical devices use causees beauty or aesthetic effects and have with the storyline.